The Effectiveness of the Role of School Leadership in Data-Driven Planning on Education Quality at SDN Cobanblimbing I Wonorejo Pasuruan - Linggasari, Henny Dwi Linggasari; Ahmad Thohirin; M. Furqon Wahyudi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Improving the quality of elementary education requires effective school leadership that is able to utilize data as a basis for decision making and school planning. This study aims to analyze the effectiveness of the principal’s leadership role in data-based planning in improving educational quality at SDN Cobanblimbing I Wonorejo, Pasuruan Regency. The study employed a descriptive qualitative approach, with data collected through document analysis, interviews, and observations. The main data sources included the Education Report Platform data from 2023 to 2025, National Assessment results, and school planning documents. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the principal played an effective role in implementing data-based planning through the systematic and collaborative use of educational quality data to identify priority areas, formulate school programs, allocate resources, and monitor implementation. The implementation of data-based planning had a positive impact on improving educational quality, as reflected in the increased achievement of Education Report indicators from 2023 to 2025, particularly in learning quality, literacy and numeracy outcomes, and the school learning climate. These findings confirm that data-informed principal leadership contributes significantly to targeted and sustainable school improvement by fostering a culture of continuous improvement and evidence-based decision making among teachers and school stakeholders. This study provides empirical insights into the implementation of data-based leadership at the elementary school level and may serve as a reference for school leaders and policymakers in strengthening evidence-based leadership practices to support national education quality improvement initiatives.